On Her Majesty's secret service [videorecording (Blu-Ray)] - Lazenby, George; Rigg, Diana; Savalas, Telly, 1924-1994; Ferzetti, Gabriele, 1925-2015 (20th Century Fox Home Entertainment, 2015)
James Bond goes undercover in the treacherous Swiss Alps to stop evil genius Blofeld from realizing a germ warfare plot that could kill millions!